2013
DOI: 10.1016/j.ejmp.2012.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation and measurement of radiation leakage from applicators used in external electron radiotherapy

Abstract: External electron radiotherapy is performed using a cone or applicator to collimate the beam. However, because of a trade-off between collimation and scattering/bremsstrahlung X-ray production, applicators generate a small amount of secondary radiation (leakage). We investigate the peripheral dose outside the radiation field of a Varian-type applicator. The dose and fluence outside the radiation field were analyzed in a detailed Monte Carlo simulation. The differences between the calculation results and data m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…A recent investigation with Monte Carlo has been reported by Shimozato et al (13) They calculated the fluence distributions and the dose distributions outside the applicator for a Varian‐type applicator, Clinac 2100CD. They found that the out‐of‐field dose was about 1% of maximal central axis dose for 16 MeV electron beam.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent investigation with Monte Carlo has been reported by Shimozato et al (13) They calculated the fluence distributions and the dose distributions outside the applicator for a Varian‐type applicator, Clinac 2100CD. They found that the out‐of‐field dose was about 1% of maximal central axis dose for 16 MeV electron beam.…”
Section: Discussionmentioning
confidence: 99%
“…However, Shimozato et al (13) have reported that the bremsstrahlung spectrum outside Varian applicators have a peak around 250 KeV, 350 KeV, 500 KeV, 750 KeV, and 1 MeV for 4 MeV, 6 MeV, 9 MeV, 12 MeV, and 16 MeV electron beams, respectively. So we used three different dosimeter types to compare their responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dose leakage from electron therapy has been the subject of limited investigation 1 , 2 , 3 , 4 , 5 , 6 A better understanding of the magnitude of out‐of‐field dose associated with this treatment modality is needed, particularly for newer models of linear accelerator. The importance of studying this issue was made clear by Yeboah et al, (7) who showed very high out‐of‐field doses when utilizing electron therapy, often largely exceeding out‐of‐field doses from comparable photon treatment fields.…”
Section: Introductionmentioning
confidence: 99%